Experiential Learning in Sociology : The Grounded Assignment and Tutorial System (GATS) Approach. - Patterson, Annette; Bell, James (Australian Learning and Teaching Council (ALTC), 1997)
This is a final report for a 1997-1998 National Teaching Development Grant funded by the Committee for University Teaching and Staff Development. The report details the GATS project and provides justification and educational rationale its development.